Pengaruh Tingkat Pengangguran Dan Tingkat Kemiskinan Terhadap Pertumbuhan Ekonomi Di Provinsi Lampung (2013-2023) - Ria Amelia; Rizki Putra Kemala Intan; Sahla Putri Vanessa; Muhammad Kurniawan (STIKes Ibnu Sina Ajibarang, 2024)
Poverty is a development problem that must be minimized because it can cause various social problems. Based on existing theories and several studies that have been conducted, the problem of poverty is generally related to several factors such as the quality of human resources, unemployment and economic growth. This research was conducted to determine the effect of unemployment and poverty levels on economic growth in Lampung province in (2013-2023). The main aim of this research was to determine the level of unemployment and poverty on economic growth in Lampung province. The method used in this research is a quantitative method. The data used is data from BPS